Acoustic properties of glass fiber assembly-filled honeycomb sandwich panels. (1st July 2016) - Yang, Yong; Li, Binbin; Chen, Zhaofeng; Sui, Ni; Chen, Zhou; Saeed, Muhammad-Umar; Li, Yufang; Fu, Renli; Wu, Cao; Jing, Yun
Abstract: A new composite structure (glass fiber assembly-filled honeycomb sandwich panel) is prepared in order to improve the acoustic properties. Effect of glass fiber assembly with different filling shapes (random and fiber ball), fiber diameter, fiber content and air-layer on acoustic properties are explored. Sound absorption coefficient (SAC) and sound transmission loss (STL) are determined by a B&K impedance tube. The experiment results indicate that the first resonance frequency of SAC disappears along with the improvement of the second resonance frequency by reducing the fiber diameter or increasing the fiber content. STL can be improved by the increase of the fiber content. Random glass fiber assembly with the fine fibers has the best STL in the all testing samples. The advantage of glass fiber assembly for improving the STL of honeycomb sandwich panel is particularly clear at frequencies below 4.5 kHz. Especially, the STL difference reaches the maximum at around 20 dB at frequencies below 3.0 kHz.